Analisis Unjuk Kerja Boiler Feed Pump Turbine Untuk Kapasitas Ketel Uap 2000 Ton/Jam Di PLTU Cirebon Jawa Barat - Sukamta, Sukamta; Sudarja, Sudarja; Wathon, Muhammad Mujaddid Ighna (Semesta Teknika, 2015)
Boiler feed pump turbine (BFPT) has an important role in the circulating of demin water from deaerator to the separator of steam power plant operations (PLTU) in Cirebon. Flow rate, temperature and pressure were important parameters in boiler feed pump process. Based on the BFPT function, it was necessary to do the analysis interpretation of the performance BFPT. Data needed for evaluation include pressure and temperature on the suction, pressure and temperature on the discharge, and flow capacity. In this study, the data were taken starting in January to December 2014. Data processing was performed using a centrifugal pump calculations, presented in tables and graphs using MS Excel. Analysis of data using qualitative interpretation of quantitative data. BFPT efficiency during operations in 2014 decreased in February - March amounted to 17.91% (BFPT A) and 18.04% (BFPT B). BFPT A highest efficiency obtained in January amounted to 73.76%, the lowest in March amounted to 55.45%. The highest efficiency BFPT B in February amounted to 72.94%, the lowest in March amounted to 54.9%. Change of Performance BFPT occur due to changes load generator power plant that led to the pressure change and flow capacity. Other factors that degrade the performance because BFPT was operated continuously for 24 hours and the age of BFPT sufficient old cause decrease in pump performance.